Quantitative analysis of the interplay between InAs quantum dots and wetting layer during the GaAs capping process. (18th September 2017) - González, D; Braza, V; Utrilla, A D; Gonzalo, A; Reyes, D F; Ben, T; Guzman, A; Hierro, A; Ulloa, J M
Abstract: A procedure to quantitatively analyse the relationship between the wetting layer (WL) and the quantum dots (QDs) as a whole in a statistical way is proposed. As we will show in the manuscript, it allows determining, not only the proportion of deposited InAs held in the WL, but also the average In content inside the QDs. First, the amount of InAs deposited is measured for calibration in three different WL structures without QDs by two methodologies: strain mappings in high-resolution transmission electron microscopy images and compositional mappings with ChemiSTEM x-ray energy spectrometry. The area under the average profiles obtained by both methodologies emerges as the best parameter to quantify the amount of InAs in the WL, in agreement with high-resolution x-ray diffraction results. Second, the effect of three different GaAs capping layer (CL) growth rates on the decomposition of the QDs is evaluated. The CL growth rate has a strong influence on the QD volume as well as the WL characteristics. Slower CL growth rates produce an In enrichment of the WL if compared to faster ones, together with a diminution of the QD height. In addition, assuming that the QD density does not change with the different CL growth rates, an estimation of the average In content inside the QDs is given. The high Ga/In intermixing during the decomposition of buried QDs does not only trigger a reduction of the QD height, but above all, a higher impoverishment of the In content inside the QDs, therefore modifying the two most important parameters that determine the optical properties of these structures.